Anti‐viral effects of interferon‐λ3 on hepatitis B virus infection in cell culture. Issue 3 (5th January 2020) - Yamada, Norie; Murayama, Asako; Shiina, Masaaki; Aly, Hussein Hassan; Iwamoto, Masashi; Tsukuda, Senko; Watashi, Koichi; Tanaka, Tomohisa; Moriishi, Kohji; Nishitsuji, Hironori; Sugiyama, Masaya; Mizokami, Masashi; et al.
Abstract : Aim: Interferon (IFN)‐λ3 is known to have antiviral effects against various pathogens. Recently, it has been reported that the production of IFN‐λ3 in colon cells after the administration of nucleotide analogs is expected to reduce hepatitis B surface antigen in chronic hepatitis B patients. Here, we aimed to prove the antiviral effects of IFN‐λ3 on hepatitis B virus (HBV) by using an in vitro HBV production and infection system. Methods: We used HepG2.2.15‐derived HBV as an inoculum and the replication‐competent molecular clone of HBV as a replication model. Results: By administering IFN‐λ3 to HepG2 cells transfected with the HBV molecular clone, the production of hepatitis B surface antigen and hepatitis B core‐related antigen was reduced dose‐dependently. IFN‐λ3 treatment also reduced the number of HBV‐positive cells and the synthesis of covalently closed circular DNA after infection of HepG2.2.15‐derived HBV to sodium taurocholate cotransporting polypeptide‐transduced HepG2 cells. The inhibitory effect on HBV infection by IFN‐λ3 was confirmed by using a recombinant a HBV reporter virus system. To elucidate the underlying mechanisms of the anti‐HBV effect of IFN‐λ3, we assessed the transcription of HBV RNA and the production of core‐associated HBV DNA in HBV molecular clone‐transfected HepG2 cells, and found that both parameters were reduced by IFN‐λ3. Conclusions: We observed that the administration of IFN‐λ3 inhibits HBV infection and the production of HBV proteins at the HBV RNA transcription level. This finding provides novel insight into the treatment of chronic hepatitis B patients with the administration or induction of IFN‐λ3.